Comparative phenotypic and genotypic virulence of Salmonella strains isolated from Australian layer farms - McWhorter, Andrea R.; Chousalkar, Kapil K. (Frontiers in Microbiology, 2015)
There are over 2,500 Salmonella enterica serovars that circulate globally. Of these, serovars those classified into subspecies I are the most common cause of human salmonellosis. Many subspecies I Salmonella serovars are routinely isolated from egg farm environments but are not frequently associated with causing disease in humans. In this study, virulence profiles were generated for ten strains of Salmonella enterica isolated directly from egg farm environments to investigate their potential public health risk. Three virulence parameters were assessed including in vitro invasion, in vivo pathogenicity and characterization of genomic variation within five specific pathogenicity islands. These ten Salmonella strains exhibited significant differences in invasion into the human intestinal epithelial cell line, Caco2. Low, moderate, and high invasion patterns were observed and the degree of invasion was dependent on bacterial growth in a nutritive environment. Interestingly, two Salmonella strains, S. Adelaide and S. Bredeney had consistently low invasion. The S. Typhimurium definitive types and S. Virchow exhibited the greatest cell invasion following growth in Luria Bertani broth. Only the S. Typhimurium strains caused disease in BALB/c mice, yet the majority of serovars were consistently detected in feces over the 21 day experiment. Genomic comparison of the five specific pathogenicity islands has shown that variation in virulence is likely multifactorial. Sequence variability was observed primarily in strains with low virulence. In particular, genes involved in forming the structures of the SPI-1 and SPI-2 type 3 secretion systems as well as multiple effector proteins were among the most variable. This variability suggest that serovars with low virulence are likely to have both invasion and within host replication defects that ultimately limit their pathogenicity.